Sub‐threshold autism traits: The role of trait emotional intelligence and cognitive flexibility. (15th May 2013) - Gökçen, Elif; Petrides, Konstantinos V.; Hudry, Kristelle; Frederickson, Norah; Smillie, Luke D.
<x xml:space="preserve">Abstract</x> Theory and research suggests that features of autism are not restricted to individuals diagnosed with autism spectrum disorders (ASDs), and that autism‐like traits vary throughout the general population at lower severities. The present research first investigated the relationship of autism traits with trait emotional intelligence and empathy in a sample of 163 adults aged between 18 and 51 years (44% male). It then examined performance on a set of tasks assessing social cognition and cognitive flexibility in 69 participants with either high or low scores on ASD traits. Results confirm that there is pronounced variation within the general population relating to ASD traits, which reflect similar (though less severe) social‐cognitive and emotional features to those observed in ASDs.